Environmental Disasters and Individuals' Emergency Preparedness: In the Perspective of Psychology and Behavior - Hong, Yuxiang; Han, Ziqiang; Kim, Jong-Suk; Lee, Joo-Heon (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Environmental disasters are becoming more frequent. These disasters not only include the most common natural disasters, but also include man-made disasters, such as public health, accident disasters, etc., which have caused greater damage to human society and cities. Because of the limitations of a single government-led model in emergency response, the emergency preparedness of communities, families and individuals are more important. In particular, the emergency preparedness psychology and behavior of individuals directly determine whether or not they can effectively protect themselves and their families in the first time of disaster. This Special Issue focuses on environmental disasters and individuals' emergency preparedness in the perspective of psychology and behavior.